Born or Made: Weighing Up Nature vs Nurture Complexities in Choosing Islamic Boarding School Leaders - Supriyono, Supriyono; Rahmah, Tazkia Aulia; Hermansyah, Eka (UIII Press, 2023)
One fundamentally plagued debate on leadership is whether leaders are born or made: nature vs nurture. Existing studies have either supported or opposed each of the arguments. Yet the literature that discusses this topic in the educational context is still limited. Despite the condition, an interesting tradition has been practiced within Indonesia’s Islamic boarding schools—colloquially known as pesantren—where in appointing its leaders, most of them depend on heredity. This study aims to garner the responses of pesantren future leaders about the hereditary leadership system in pesantren, focusing on perception, reflection and projection inquiries. This phenomenological study relies on in-depth interviews to collect the data, whilst employing triangulation of the data sources with three pesantren future leaders in East and Central Java. The findings show that by weighing up the positive and negative implications of the pesantren’s hereditary leadership, converging it with the meritocratic system appears to be salutary, given it ticks all the boxes of three human developmental facets: physical (leadership gen), cognitive (intellectual ability) and socio-emotional (moral integrity). In this regard, the hereditary-meritocratic convergence system could help pesantren run its leadership selection with both nature (intrinsic) and nurture (extrinsic) deliberations, as supported by the Western-secular and Islamic scientific discourses. Yet, despite the positive outcome, it also leaves a critical question on the side of the meritocratic system on why meritocracy dismisses genetic considerations given studies have proved that leadership is indeed influenced by both genetics and environment. The findings call for further investigation on the hereditary-meritocratic convergence system in choosing school leaders—especially in the pesantren context—that despite the meritocracy, heredity, too, could be a pivotal cogitation.